POSSIBLE WAYS TO SAVE SEED PRODUCTION OF PEA DOMESTIC VARIETIES IN CURRENT CONDITIONS - N. A. Samarin; S. N. Samarin (Овощи России, 2015)
The possible ways of development of seed production of pea in Russia and increasing of competitive growth of domestic pea varieties suitable for processing industry are represented in the article.